Pemanfaatan Buah Mangrove Rhizophora apiculata Sebagai Olahan Kopi Mangrove Dalam Upaya Peningkatan Ekonomi Masyarakat Di Desa Maitara Utara Kecamatan Tidore Utara - Salim Abubakar; Masykhur Abdul Kadir; Riyadi Subur; Rina; Ariyati H. Fadel; M. Said Al Hadad; Nurhalis Wahidin; Adi Noman Susanto; Fajria Dewi Salim; Darmiyati Muksin (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The use of mangrove fruit as food and beverage ingredients has never been carried out by the people of Maitara Island, Tidore City Islands. The problems faced by the community are: low public knowledge about the benefits of mangrove fruit as a food and beverage ingredient, lack of public knowledge about the diversification of processed mangrove fruit products as an ingredient in mangrove coffee drinks and low knowledge of good quality mangrove coffee powder processing techniques. The objectives of the PKM activities are: partners can find out about the benefits of mangrove fruit as food and beverage ingredients, apply appropriate technology in mangrove coffee powder processing techniques with good quality and get quality mangrove coffee variants and have high selling value to increase partner's economic income. The results of PKM activities are the diversification of Rhizophora apiculata processed mangrove fruit products as mangrove coffee drink ingredients that have a selling value so that they can improve people's welfare, the mangrove fruit calyx produces finer and denser coffee powder, coffee powder can be served in various variants, namely Sory (original soki ), SoSweet (sweet soki) and Pelakor (spice coffee customer) and all are liked by the public and organoleptic test results, all types of coffee variants are liked by researchers and the Pelakor variant is the variant that has a higher scoring value.